2016
DOI: 10.1055/s-0042-119041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metformin on Endocrine and Metabolic Parameters in Patients with Polycystic Ovary Syndrome

Abstract: The present study was designed to evaluate the effects of metformin on metabolic and endocrine parameters in patients with polycystic ovary syndrome (PCOS). The study included 40 patients with PCOS. Patients were divided into 2 groups based on whether they will receive metformin (500 mg 3 times a day, n=20) or placebo (n=20) for 3 consecutive months. Serum concentrations of fasting blood glucose, insulin, HOMA-IR, INSL-3, visfatin, FSH, and LH were measured at baseline and after 3 months of therapy. The key en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Totally 489 relevant literatures were searched, among of which we excluded 46 duplicates, 26 non‐English literatures, 48 letters or reviews, and the remaining 369 articles were further assessed with the exclusion of 99 non‐human studies, 112 unrelated to PCOS, 128 unrelated to insulin‐sensitizing drugs, 2 without data, or incomplete data literatures. Finally, 28 RCTs published from 2001 to 2017 met our inclusion criteria were included in this network meta‐analysis (Figure ), which included 1328 PCOS patients. Among of the 28 RCTs, the population of 23 RCTs was from Caucasians and that of five RCTs was from Asians.…”
Section: Resultsmentioning
confidence: 99%
“…Totally 489 relevant literatures were searched, among of which we excluded 46 duplicates, 26 non‐English literatures, 48 letters or reviews, and the remaining 369 articles were further assessed with the exclusion of 99 non‐human studies, 112 unrelated to PCOS, 128 unrelated to insulin‐sensitizing drugs, 2 without data, or incomplete data literatures. Finally, 28 RCTs published from 2001 to 2017 met our inclusion criteria were included in this network meta‐analysis (Figure ), which included 1328 PCOS patients. Among of the 28 RCTs, the population of 23 RCTs was from Caucasians and that of five RCTs was from Asians.…”
Section: Resultsmentioning
confidence: 99%
“…For metformin, there was an unexpected borderline statistically significant positive association with meningioma risk in analyses matched on duration of diabetes and level of glycemic control, which was rendered statistically significant in the test for trend restricted to women. Possibly, metformin use leads to hormonal changes in women, such as reduction of luteinizing or follicle stimulation hormone as observed in polycystic ovary syndrome [ 23 ], which may influence free estradiol levels and thereby risk of meningioma. In addition, although we adjusted our analyses for BMI, we cannot fully exclude residual confounding by adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we performed a randomized, placebo-controlled study to assess the effectiveness of metformin in metabolic and endocrine alteration in women with PCOS [32]. Our data suggested that treatment with metformin causes a significant reduction in androgen levels as well as serum visfatin in women with PCOS relative to the controls.…”
Section: Introductionmentioning
confidence: 87%